Espiritualidade feminina e transformações no campo religioso: um estudo sobre círculos de mulheres no Brasil sob a influência do feminismo e da Nova Era - Kris, Karina Babuch (2023)
Religious practices and their studies, particularly from the late 20th century onwards, have been strongly influenced by movements such as Feminism and the New Age, bringing significant conceptual shifts and possibilities that have transformed behaviors and some research models, with a focus on the impact of these transitions from women's perspectives. As a result, in the West, new religious movements emerged advocating for women and the feminine. Specifically, a group known as the Women’s Circles, perceived today as a global movement that is growing in Brazil, carries at its core conceptions of the sacredness of the feminine intertwined with political, social, and psychological issues. This research aims to trace the historical context of this group and understand, with the contribution of Feminism and the New Age, the prospects of this movement in Brazil. Additionally, interviews were conducted with key figures in the movement, and ethnographic observations were carried out to explore the results that emerged from the research. The research results indicate the intersection of feminism and aspects of the New Age in the movement. Furthermore, they demonstrate that this construct provides women with an identity-based spiritual space that utilizes female deities and positions them at a central place. The study is concluded with some considerations about its limitations, as well as recommendations for future research